Assessment of load influence of the Akademik Vernadsky Antarctic station on the quality of adjacent marine area - Bondar, S. (Ukrainian Antarctic Journal, 2003)
Abstract. Discharge of pollutants into Argentine Archipelago marine environment is assessed and the discharge loads are calculated as a follow-up of the work performed at the Ukrainian Antarctic Station “Akademik Vernadsky”. The calculations were made on the basis of the model used for development of “The Procedure for Accelerated Inventory of Environmental Pollution Sources”. Basic points of the used method-model are described to show its capacity to develop the measures and priorities to reduce pollution of the adjacent sea areas. Comparison is made between the calculated discharge value and the experimental data. The proper comparison of calculated data with experimental results makes it possible to come to the conclusion about the possibility to use the Procedure in practice to assess the effect of the Ukrainian Antarctic Station on the marine environment. The nomograms presented in the paper/report can be used for such assessment.